STRATEGIES OF THE SME COOPERATIVE OFFICE AND TRADE INDUSTRY IN SUMENEP REGENCY FOR ACCELERATING HALAL CERTIFICATION: A MASLAHAH MURSALAH PERSPECTIVE - Wardah, Elisa; Nahidloh, Shofiyun; Fajar, Fajar (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2024)
This study examines the strategies implemented by the Sumenep District Office of Cooperatives, SMEs, Industry, and Trade (DiskopUKMPerindag) to accelerate the halal certification program, guided by the framework of Law Number 33 of 2014 on Halal Product Guarantee. Using a qualitative approach, data were collected through field surveys, interviews, and documentation involving DiskopUKMPerindag officials and MSME actors under their guidance who have obtained halal certification.The analysis adopts a normative approach based on the principle of Maslahah Mursalah, exploring its application in the regulation and implementation of halal certification. The findings reveal that halal certification not only aligns with Islamic sharia but also enhances consumer trust, expands market share, and increases profitability for certified products. The principle of Maslahah Mursalah serves as a flexible normative foundation, addressing societal needs by ensuring that halal regulations go beyond legal compliance to support community welfare and benefit.This research underscores the importance of halal certification in driving local economic growth, improving product quality, and boosting consumer confidence. By accelerating the certification program, DiskopUKMPerindag Sumenep strengthens the competitiveness of SMEs, promotes community welfare, fosters local economic development, and ensures adherence to Islamic law.